KEEFEKTIFAN TEAMS GAMES TOURNAMENT DAN MAKE A MACTH DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Nurwidia, Anita; Haryanto, Samsi; Mulyoto, Mulyoto (Annals of Mathematical Modeling, 2019)
Tujuan penelitian ini adalah (1) Untuk mengetahui perbedaan pengaruh penerapan model Teams Games Tournament dan Make A Macth terhadap hasil belajar Matematika; (2) Untuk mengetahui perbedaan pengaruh siswa yang memiliki aktivitas tinggi dengan siswa yang memiliki aktivitas rendah terhadap hasil belajar Matematika; dan (3) Untuk mengetahui interaksi pengaruh model Teams Games Tournament dan Make A Macth dengan aktivitas belajar tinggi dan rendah terhadap hasil belajar Matematika. Penelitian ini merupakan penelitian ekspererimen. Teknik pengumpulan data menggunakan kuesioner dan soal tes pilihan ganda. Analisis data yang digunakan adalah analisis varians dua jalan. Hasil penelitian menunjukkan: (1) Terdapat perbedaan pengaruh model Teams Games Tournament dan Make A Macth terhadap hasil belajar Matematika (2) Terdapat perbedaan pengaruh siswa yang memiliki aktivitas tinggi dan rendah terhadap hasil belajar Matematika. (3) Tidak terdapat interaksi pengaruh model Teams Games Tournament dan Make A Macth dengan aktivitas belajar tinggi dan rendah terhadap hasil belajar Matematika. The methode of effectivenses teams games tournament and make a match to encourage the result of mathematics seem fromactivities study AbstractThe purpose of this study are (1) To know whether there were the differences of influences of the Teams Games Tournament and Make A Match methods for the result study of mathematics; (2) To know whether there were the differences the influences the activities study were high and low for the result study of mathematics; and (3) To know whether there were the influences of interaction Teams Games Tournament and Make A Match methods also the activities study were high and low for the result study of mathematics . This research is a eksperiment research. Data collection techniques used questionnaires and multiple choice test questions. Data analysis used is anava two way. The results showed: (1) there were the differences of influences methods for Teams Games Tournament and Make A Match. The learning methods Make A Match more good to improve the result study of mathematics then learning methods Teams Games Tournament. (2) there were the differences of students? influences that had high activities with low activities on the result study of mathematics. Based on the analyse result, the high students? activities more good to improve the result study of mathematics then the low students; activities (3) there were not the interaction of the influences learning methods Teams Games Tournament and Make A Match with the activities study on the result study of mathematics